Factors associated with modern contraceptives use among postpartum women in Bukombe district, Geita region, Tanzania - Mahande, Michael Johnson (PLoS One, 2020)
INTRODUCTION: Modern contraceptive use during the first year postpartum potentially prevents unplanned pregnancies and help to improve maternal and child health. Therefore, identifying factors associated with contraceptive utilization among women of reproductive age during extended postpartum period is essential. OBJECTIVE: This study aimed to assess factors associated with modern contraceptives use among postpartum women in Bukombe District, Geita region. METHOD: A community-based cross-sectional study was conducted among women who were in their first year after child birth in Bukombe district. A total of 511 women were included using multistage sampling techniques. Data were collected using a structured questionnaire. Data analysis was performed using Stata 15 (College Station, Texas, USA). RESULTS: The prevalence of postpartum modern contraceptive was 11.9%. The most frequently used method was implant (6.5%). Most women started to use the contraceptive during the first three months after delivery. Living in urban (AOR = 1.85, 95% CI: 1.20–3.79), having business (AOR = 2.35, 95% CI: 1.31–2.28), last born aged 3–4 months (AOR = 3.31, 95% CI: 1.11–9.85) and menses resumption (AOR = 9.24, 95% CI: 3.60–23.72) were predictors for postpartum contraceptive use. However, fear of side effects, poor knowledge about contraceptives, husband restrictions, distance to health facility and contraceptive availability were reported as barriers for postpartum modern contraceptive use. CONCLUSION: Prevalence of postpartum modern contraceptive use in the study area is still low. Numerous factors were reported as barriers for postpartum contraceptive use. A strategy such as health education on befits of post-partum modern contraceptive use and counseling women about side effects may help to improve its uptake.